A review on optical actuators for microfluidic systems. (7th November 2017) - Yang, Tie; Chen, Yue; Minzioni, Paolo
Abstract: During the last few decades microfluidic systems have become more and more popular and their relevance in different fields is continually growing. In fact, the use of microchannels allows a significant reduction of the required sample-volume and opens the way to a completely new set of possible investigations, including the study of the properties of cells, the development of new cells' separation techniques and the analysis of single-cell proteins. One of the main differences between microscopic and macroscopic systems is obviously dictated by the need for suitable actuation mechanisms, which should allow precise control of microscopic fluid volumes and of micro-samples inside the fluid. Even if both syringe-pump and pneumatic-pump technologies significantly evolved and they currently enable sub- μ L samples control, completely new approaches were recently developed for the manipulation of samples inside the microchannel. This review is dedicated to describing different kinds of optical actuators that can be applied in microfluidic systems for sample manipulation as well as for pumping. The basic principles underlying the optical actuation mechanisms will be described first, and then several experimental demonstrations will be reviewed and compared.